Синтез ДНК в интактных митохондриях кукурузы, обработанных бактериальными векторными плазмидами серии pBR - Константинов, Ю.М.; Подсосонный, В.А.; Луценко, Г.Н.; Ривкин, М.И. (Биополимеры и клетка, 1989)
Установлена возможность транслокации бактериальных векторных плазмид pBR327 и pBR322 во внутреннее пространство изолированных митохондрий проростков кукурузы. С использованием радиоавтографического анализа обнаружена матричная активность плазмиды pBR322 в отношении синтеза ДНК в генетической системе интактных митохондрий кукурузы. Встановлено можливість транслокації бактерійних векторних плазмід pBR327 і pBR322 у внутрішній простір ізольованих мітохондрій проростків кукурудзи. З використанням радіоавтографічного аналізу виявлено матричну активність плазміди pBR322 стосовно синтезу ДНК у генетичній системі інтактних мітохондрій кукурудзи. Fractions of high-molecular weight («chromosomal») and plasmid-like DNA from the isolated maize seedling mitochondria are synthesized with different rate. DNA of bacterial vector pBR327 and pBR322 plasmids is shown to be translocated into inner space of isolated mitochondria. Radioautographic analysis has been used to find the matrix activity of the supercoiled pBR322 plasmid to synthesize DNA in the system of intact maize mitochondria. The model system described is assumed to be used to study th« problems of replication and transcription of recombinant plasmid DNA in the plant mitochondria.